Intramuscular and Intradermal Electroporation of HIV-1 PENNVAX-GP® DNA Vaccine and IL-12 Is Safe, Tolerable, Acceptable in Healthy Adults - Srilatha Edupuganti; Stephen C. De Rosa; Marnie Elizaga; Yiwen Lu; Xue Han; Yunda Huang; Edith Swann; Laura Polakowski; Spyros A. Kalams; Michael Keefer; Janine Maenza; Megan C. Wise; et al. (Vaccines, 2020)
Background: Several techniques are under investigation to improve the immunogenicity of HIV-1 DNA vaccine candidates. DNA vaccines are advantageous due to their ease of design, expression of multiple antigens, and safety. Methods: The HVTN 098 trial assessed the PENNVAX®-GP DNA vaccine (encoding HIV env, gag, pol) administered with or without plasmid IL-12 at 0-, 1-, 3-, and 6-month timepoints via intradermal (ID) or intramuscular (IM) electroporation (EP) in healthy, adult participants. We report on safety, tolerability, and acceptability. Results: HVTN 098 enrolled 94 participants: 85 received PENNVAX®-GP and nine received placebo. Visual analog scale (VAS) pain scores immediately after each vaccination were lower in the ID/EP than in the IM/EP group (medians 4.1–4.6 vs. 6–6.5, p < 0.01). IM/EP participants reported greater pain and/or tenderness at the injection site. Most ID/EP participants had skin lesions such as scabs/eschars, scars, and pigmentation changes, which resolved within 6 months in 51% of participants (24/55). Eighty-two percent of IM/EP and 92% of ID/EP participant survey responses showed acceptable levels of discomfort. Conclusions: ID/EP and IM/EP are distinct experiences; however, HIV-1 DNA vaccination by either route was safe, tolerable and acceptable by most study participants.